2020
DOI: 10.3390/molecules25245854
|View full text |Cite
|
Sign up to set email alerts
|

Panax quinquefolius (North American Ginseng) Polysaccharides as Immunomodulators: Current Research Status and Future Directions

Abstract: Panax quinquefolius (North American ginseng, NAG) is a popular medicinal plant used widely in traditional medicine. NAG products are currently available in various forms such as roots, extracts, nutraceuticals, dietary supplements, energy drinks, etc. NAG polysaccharides are recognized as one of the major bioactive ingredients. However, most NAG reviews are focused on ginsenosides with little information on polysaccharides. NAG polysaccharides have demonstrated a therapeutic activity in numerous studies, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 120 publications
(227 reference statements)
0
18
0
Order By: Relevance
“…On the one hand, studies reported that ginsenosides Rb1 could stimulate the phagocytic capacity of macrophages for bacteria via activation of the Fcgamma receptors and p38/Akt pathway (48), while the combination use of ginsenoside Rg3, Rk1, Rg5 could stimulate immune reactions through nuclear factor-kappa B (NF-kB) and cytokine secretion (49,50). In addition, polysaccharides could potentially activate receptors like Toll-like receptors (TLRs), Ctype lectin receptors, and so on (51), which are the key receptors related to intestinal immunity against pathogen (52,53). On the other hand, many studies have suggested that even though polysaccharides is non-digestible, it was still used as immunomodulator.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, studies reported that ginsenosides Rb1 could stimulate the phagocytic capacity of macrophages for bacteria via activation of the Fcgamma receptors and p38/Akt pathway (48), while the combination use of ginsenoside Rg3, Rk1, Rg5 could stimulate immune reactions through nuclear factor-kappa B (NF-kB) and cytokine secretion (49,50). In addition, polysaccharides could potentially activate receptors like Toll-like receptors (TLRs), Ctype lectin receptors, and so on (51), which are the key receptors related to intestinal immunity against pathogen (52,53). On the other hand, many studies have suggested that even though polysaccharides is non-digestible, it was still used as immunomodulator.…”
Section: Discussionmentioning
confidence: 99%
“…It is native to eastern North America and widely inhabits several Canadian and US states. Along with ginsenosides, polysaccharides have been identified as one of the major bioactive ingredients in American ginseng, and polysaccharides may possess paradoxical immunostimulatory and immunosuppressive properties (16). A multisite, double-blind randomized trial in which cancer survivors with fatigue (n = 364) took 2,000 mg of American ginseng vs. a placebo for 8 weeks was conducted to evaluate the efficacy of American ginseng on CRF (17).…”
Section: Fatiguementioning
confidence: 99%
“…As published in 2020, the structural characteristics and immunomodulatory properties of American ginseng polysaccharides have been summarized [ 21 ]. In this review, we summarize the structural features of polysaccharides from American ginseng from all publications until April 2021, which are listed in Table 2 .…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…At present, approximately 200 active substances in these three species have been discovered, including saponins [ 6 , 7 , 8 ], polysaccharides [ 9 , 10 ], oligosaccharides [ 11 , 12 ], polyacetylenes [ 13 , 14 ], peptides [ 15 , 16 ], and bioactive proteins [ 17 ]. Polysaccharides are the main active components and have demonstrated diverse pharmacological functions, such as anti-tumor [ 18 , 19 ], immune system modulation [ 20 , 21 , 22 , 23 ], anti-oxidant [ 24 , 25 ] and anti-aging [ 26 ] activities, as well as others [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%